Enhancing the performance of konjac glucomannan films through incorporating zein–pectin nanoparticle-stabilized oregano essential oil Pickering emulsions. (March 2022) - Zhang, Shikai; He, Ziyang; Xu, Fangzhou; Cheng, Yue; Waterhouse, Geoffrey I.N.; Sun-Waterhouse, Dongxiao; Wu, Peng
Abstract: To address the limitations of existing konjac glucomannan (KGM)-based films, KGM films activated by zein–pectin nanoparticle-stabilized oregano essential oil Pickering emulsions (ZPEOs) were prepared. Results showed that the hydrophilicity/hydrophobicity of KGM films can be tuned through adjusting the ZPEO concentration. ZPEO addition altered the hydrogen bonding, electrostatic interactions and hydrophobic effects among film components. The ZPEO-KGM composites behaved as high-performance films with good uniformity, compatibility, along with antioxidant, antibacterial and fruit preservation properties. Increasing ZPEO content in ZPEO-KGM films increased the elongation at break, DPPH free radical scavenging and antibacterial effect and decreased water vapor permeability. The ZPEO-KGM films with ZPEO-to-KGM ratios of 50 : 50 and 60 : 40 had the highest tensile strength (30.98 MPa) and water contact angle (93.56°), respectively. The essential oil in the ZPEO-KGM film can be slowly released for 21 days or even longer. This research demonstrates the plasticizing effect of ZPEO and potential of ZPEO-KGM films for food preservation/packaging. Graphical abstract: Image 1 Highlights: Oregano essential oil (OEO) was stabilized by zein-pectin nanoparticles (ZPNPs). Konjac glucomannan (KGM) films were activated by ZPNP-OEO Pickering emulsion (ZPEO). KGM-ZPEO films showed superior mechanical and water barrier properties. KGM-ZPEO films exhibited antioxidant, antibacterial and fresh-keeping effects. Adding ZPEO to KGM films led to high-performance films for fruit preservation.